INSURANCE OF COMMERCIAL BANKS' CREDIT FACILITIES AND CREDIT RISK MANAGEMENT - Zokir Mamadiyarov; O‘tkirjon Tajimatov (Journal of Artificial Intelligence and Digital Economy, 2024)
The practice of insurance of credit facilities of commercial banks is an important means of credit risk management in banking activities. Through insurance, banks can protect their loan portfolio from risks and reduce losses related to customers who face default or other debt situations. Development of diversified insurance products, automation of processes by introduction of technological solutions and use of international experiences are considered important for improvement of insurance practice. These approaches are of great importance in reducing credit risks and making banks more efficient. This is it in the article commerce of banks credit objects insurance to do practice improvement and on prudent credit risk management approaches and international experience analysis will be done